2015
DOI: 10.1508/cytologia.80.261
|View full text |Cite
|
Sign up to set email alerts
|

<i>Ulva partita</i> sp. nov., a Novel <i>Enteromorpha</i>-Like <i>Ulva</i> Species from Japanese Coastal Areas

Abstract: SummaryIn this report, Ulva partita Ichihara, sp. nov. (Ulvales, Ulvophyceae) was described from Japanese seashores. This species was characterized by (i) frequent branches in the basal region, but not in the middle to upper region, (ii) being up to 20 cm in height and 5 mm in diameter, and (iii) containing chloroplasts covering the outer cell wall in the middle and upper regions of thalli, but with many chloroplasts leaning to one side of the cells in the basal region. Ulva partita is distinguished from morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Comparison with other chloroplast genomes Ulva pertusa exhibits a phenotype of lettuce-like morphology similar to the morphology of U. ohnoi and U. lactuca. However, evolutionary studies on these algae have suggested that U. pertusa is closely related to U. flexuosa and U. linza, and this species has been classified into a clade separate from that containing U. ohnoi and U. lactuca (Kraft et al, 2010;Ichihara et al, 2015;Matsumoto and Shimada, 2015). Using the complete chloroplast genome sequences, we generated a phylogenetic tree of Ulva species, including U. pertusa.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison with other chloroplast genomes Ulva pertusa exhibits a phenotype of lettuce-like morphology similar to the morphology of U. ohnoi and U. lactuca. However, evolutionary studies on these algae have suggested that U. pertusa is closely related to U. flexuosa and U. linza, and this species has been classified into a clade separate from that containing U. ohnoi and U. lactuca (Kraft et al, 2010;Ichihara et al, 2015;Matsumoto and Shimada, 2015). Using the complete chloroplast genome sequences, we generated a phylogenetic tree of Ulva species, including U. pertusa.…”
Section: Resultsmentioning
confidence: 99%
“…The relation between the gamete types (type α and β) and the inheritance pattern of cp-DNA has been reported in several ulvophycean species and C. reinhardtii (Table 2). It is particularly interesting that cp-DNA is always transmit- (Ichihara et al 2015). ** Uniparental inheritance from mt + gametes.…”
Section: Resultsmentioning
confidence: 99%
“…The pairs of mt − (MGEC-2) and mt + (MGEC-1) strains of Ulva partita used were collected from the coast of Japan (Supplementary Table 7 ) 23 25 , 52 . We recently renamed this species from Ulva compressa to U .…”
Section: Methodsmentioning
confidence: 99%